2011
DOI: 10.1080/08941920903214116
|View full text |Cite
|
Sign up to set email alerts
|

General Antecedents of Personal Norms, Policy Acceptability, and Intentions: The Role of Values, Worldviews, and Environmental Concern

Abstract: Results of two studies are reported, in which we compare the predictive power of three general behavioral antecedents (i.e., values, worldviews, and environmental concern) in explaining personal norms, behavioral intentions (i.e., environmental activism), and acceptability of energy policies. Values-especially biosphericappeared to be more powerful in explaining personal norms, intentions, and policy acceptability than were worldviews and environmental concern, although these differences were in some cases not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
190
2
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(221 citation statements)
references
References 40 publications
13
190
2
16
Order By: Relevance
“…Biospheric and altruistic motivations have shown to be positively associated with the social acceptance of environmental policies (Steg et al 2005(Steg et al , 2011. Although conflicts and tensions have been reported between rural actors and management institutions in the midupper stream of the Otún River watershed (Barragán and Valdés 2011, Monsalve 2012, Rincón-Ruíz et al 2014, our results suggest that these do not result from the clash of antienvironmental motivations: rural people prioritized biospheric and altruistic motivations over egoistic ones (Table 3).…”
Section: Insights For Environmental Managementmentioning
confidence: 55%
See 2 more Smart Citations
“…Biospheric and altruistic motivations have shown to be positively associated with the social acceptance of environmental policies (Steg et al 2005(Steg et al , 2011. Although conflicts and tensions have been reported between rural actors and management institutions in the midupper stream of the Otún River watershed (Barragán and Valdés 2011, Monsalve 2012, Rincón-Ruíz et al 2014, our results suggest that these do not result from the clash of antienvironmental motivations: rural people prioritized biospheric and altruistic motivations over egoistic ones (Table 3).…”
Section: Insights For Environmental Managementmentioning
confidence: 55%
“…For instance, recent research has demonstrated the benefits of integrating environmental psychology and valuation. In doing so, motivations, also known as orientations (de Groot and Steg 2008, 2010, Steg et al 2011, are considered to be key factors determining environmental values (Kenter 2016b, Raymond andKenter 2016). Scholars have quantitatively addressed three major motivations that influence environmental attitudes and behavior: egoistic, altruistic, and biospheric (de Groot and Steg 2008, 2010, Steg et al 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular importance for this paper is the recurrent finding that individuals with self-transcendent values engage more in climate-friendly behavior and policy support than people with self-enhancing values (Corner et al 2014;Nilsson et al 2004;Biel 2007, 2008;Poortinga et al 2004;Steg et al 2011; see also Leiserowitz 2006). Furthermore, research suggests that existing value orientations may interact with environmental information.…”
Section: Valuesmentioning
confidence: 99%
“…Prior research indicates that individuals who value the well-being of larger communities-i.e., those high in self-transcendence-are more likely to harbor pro-environmental attitudes and take pro-environmental action than individuals who value personal gain and status-i.e., self-enhancement (e.g., Gagnon Thompson and Barton 1994;Karp 1996). Thus, people with strong selftranscendent value orientations tend to be more concerned about the environment and more likely to act compared to those who prize self enhancement (e.g., Garvill 2002, 2003;Schultz et al 2005;Schultz and Zelezny 1999;Slimak and Dietz 2006;Steg and de Groot 2012;Stern et al 1995;see de Groot and Steg 2008 for a review).…”
Section: Valuesmentioning
confidence: 99%